Factors influencing the prices of private housing - Teh, Kim Hwee (2014)
"Is the Property Boom Over?'', an article in Sunday Times, 24 July 1994, questioned the probability of a continued escalation in property prices in Singapore. This goes to show the inadequate ability of people to answer such a question which unfortunately is of major concern to the value of their total assets. This question has its basis on the exceptional growth in property prices over the past three years. The purpose of this project is thus to focus upon finding an answer to this question. Our emphasis, however will be on the private property prices which have soared from 91.4 points in 1989 to 227.1 points (PPI) in the second quarter of 1994.